(untitled) (World Bulletin of Public Health, 2022)
Brick factories are considered environmentally polluted areas due to the products of combustion processes, which in turn have a significant negative impact on the health of workers in those areas or those who live near them. Therefore, this study was designed to investigate those pollutants, especially gaseous ones such as carbon dioxide, carbon monoxide and nitrogen monoxide. The extent of their impact on human health, the concentration of some vital indicators for workers in that area was measured and compared with healthy people far from the pollution area, such as urea, cholesterol and triglycerides. out. As for the vital signs, they were also high in the people in that area compared to the healthy people.